Relativite, groupes et topologie - Universite de Grenoble. Ecole d'ete de Physique theorique, Les Houches; Dewitt-Morette, Cecile; Dewitt, Bryce S. (Bryce Seligman), 1923. (New York: Gordon and Breach Science Publishers, 1964)
Edited by C. DeWitt, B. DeWitt.
English or French.
Includes bibliographical references.
engfre.
Keywords: Relativity; Group theory; Gravitation